Revisiting General Philosophy and Absurdist Literature: Theory and Practice - Preeti, Dr. Sharan Pal (International Journal of Advanced Science and Technology, 2020)
Present project attempts to deliberate upon the concept of Existentialism which has been essential motif in Western Philosophy for quite some time. Significant great philosophers bestowed considerable time and and attention on this concept. It is for the sake of convenience that we may begin this with Martin Heidegger’s treatise. We will be able to read Beckett better which would lead to a greater comprehension of the profundity of Beckett’s novels since Beckett was in the main stream. He was an avid reader of western philosophy. We propose to revisit Beckett with the light of these insights. Martin Heidegger (26 September 1889 – 26 May 1976) was a German philosopher who begins with the question of being in his book Being and Time (1927). He gave the concept of Dasein in this book. It is a French term in which da stands for there and sein stands for being. In English it is translated as “Existence”. By Dasein Heidegger refers to experience of being which is particular to human beings. In this book he goes through existential analysis:“The senses do not enable us to cognize any entity in its Being; they merely serve to announce the ways in which 'external' things within-the-world are useful or harmful for human creatures encumbered with bodies....they tell us nothing about entities in their Being”.[1]